A new genus and two new species of Platyarthridae Verhoeff, 1949 (Crustacea: Isopoda: Oniscidea) from Brazil - Bezerra-Pereira, Carlos Anderson Soares; Grangeiro, Daniela Correia; Lima, Lucas Ramos Costa (Zootaxa, 2023)
A new genus and two new species of the family Platyarthridae are described from the Brazilian state of Piau, Paratrichorhina piauiensis n. gen. et n. sp. and P. taitii n. gen. et n. sp. Similarities and differences with the other genera of the family are discussed, and a key to the family is provided.